Profit-led or cost-led inflation? Propagation effects through the EU inter-industry network - Cucignatto, Giacomo; Garbellini, Nadia; Fora Alcalde, Facund (PSL Quarterly Review, 2023)
The return of persistent inflation in OECD countries has been the most significant macroeconomic phenomenon in recent years. This article analyses different explanations for the current inflationary dynamics, from which various policy recommendations arise. Specifically, by using a Multi-Regional Input-Output (MRIO) model, the article investigates whether the rise in profits and profit share is the result of changes in the behaviour of firms or just the natural outcome of rising energy costs, in the case of France, Italy and Spain. Our results indicate that companies raised prices more than necessary in order to maintain their levels of profitability in each of the European economies analysed, confirming that inflation hikes were led by surging profits. This implies that the introduction or strengthening of price controls would help to rapidly bring inflation under control, protecting the purchasing power of households.